Interface characterization of friction welded low carbon steel and copper alloys - Caligulu, Ugur; Acik, Mustafa (Carl Hanser Verlag, 2015)
In this study, the interface characterization of friction welded AISI 1010 low carbon steel and copper alloys was investigated. The friction welding tests were performed by using a direct drive type friction welding machine. After friction welding, interface regions of the welded specimens were examined by optical microscopy, SEM-EDS, and X-ray analysis to determine the microstructural changes. Microhardness and tensile tests were conducted to determine mechanical properties of the welded specimens. The experimental results indicated that AISI 1010 low carbon steel could be joined to copper using the friction welding technique for achieving a weld with sufficient strength. Tensile strength values also confirmed this result and intermetallic phases did not occur at the interface.
Keywords: AISI 1010; copper; friction welding; tensile strength; microhardness